The Study of Traffic on The Roads The Governorate Of Karbala (Journal of the College of Education for Women, 2019)
The study of traffic on the roads the governorate of Karbala, Where is the study of traffic on the roads measure is necessary to determine the extent of the road and highlighting the importance of its role in the transfer of individuals from original to destination as well as the importance of the region that attracted its movement. This research aims to analyze the traffic in the governorate of Karbala through the study and analysis of surveys of traffic that were made in the governorate. Based on this analysis, it has been reached to identify volumes of the traffic and its density and how the roads are efficient and accommodating these volumes, the results of the traffic survey of the studied roads in the area of the study have shown that the main roads of the Governorate expressing the high traffic resulted by the strong spatial relation that connects the Governorate of Karbala by the neighboring Governorates. After studying the efficiency of the roads studied, we find that by (Karbala - Najaf) has been progressed to the first stage, which means a highest level of service. The lowest roads in the level of efficiency, are (Karbala - Baghdad) and (Karbala – Ein Tammer) because of the high traffic volume on these two roads, the road of (Karbala - Baghdad) has high flow of traffic volumes of different classes of vehicles, while (Karbala – Ein Tammer) has flow of a high percentage of heavy load vehicles. This requires proving the efficiency of these two roads to cover the heavy traffic volumes flow, and to cover the potential increase in the traffic volumes on them in future.